Strategies to improve the fertility of fresh and frozen donkey semen - Oliveira, José Victor de [UNESP]; Oliveira, Pedro Victor de Luna Freire [UNESP]; Melo e Oña, Cely Marini [UNESP]; Guasti, Priscilla Nascimento [UNESP]; Monteiro, Gabriel Augusto [UNESP]; Sancler da Silva, Yamê Fabres Robaina [UNESP]; Papa, Patrícia de Mello [UNESP]; Alvarenga, Marco Antônio [UNESP]; Dell'Aqua Junior, Jose Antonio [UNESP]; Papa, Frederico Ozanam [UNESP] (Elsevier, 2016)
Fertility rates of donkey semen in jennies are lower compared to mares. The aims of this study were to evaluate different sperm cryopreservation methods and insemination strategies to improve the fertility of donkey semen in jennies. Three experiments were performed: (1) the comparison of two freezing methods of donkey semen (conventional method and automated method); (2) the determination of a suitable insemination dose of fresh donkey semen for jennies and mares; and (3) the influence of the semen deposition site on fertility of jennies inseminated with frozen donkey semen. For experiment 1, no differences were observed in total motility, angular velocity, curvilinear velocity, straight-line velocity, and plasma membrane integrity between samples frozen with the conventional (Styrofoam box) and the automated method (TK 4000C). However, the automated method provided higher values of progressive motility and rapid cells in frozen-thawed samples in comparison with the conventional method (P < 0.05). For experiment 2, mares were bred using 500 × 106 fresh sperm (M); and jennies using 1 × 109 (J1) or 500 × 106 fresh sperm (J5). Pregnancy rates in M, J1, and J5 were 93% (14/15), 73% (11/15), and 40% (6/15), respectively. When using different insemination doses, 500 × 106 or 1 × 109 sperm, no significant difference was observed in pregnancy rates of mares (M, 14/15) and jennies (J1, 11/15). Furthermore, there was no significant difference between the two insemination doses in jennies. However, with an insemination dose of 500 × 106 fresh sperm, the pregnancy rates were significantly higher in mares (M, 14/15) than in jennies (J5, 6/15; P < 0.05). For experiment 3, the inseminations were carried out in the uterine body (UB) or in the uterine horn of jennies with frozen-thawed donkey semen. No pregnancies were achieved with inseminations performed in the UB (0/12). The pregnancy rate for uterine horn group was 28.26% (13/46) and thus significantly higher than the UB group (0%; 0/12; P < 0.05). In conclusion, the automated method showed higher values on progressive motility and rapid cells parameters compared to the conventional method and can be used as an alternative for freezing donkey semen. The increase in the number of sperm cells per insemination dose using fresh donkey semen improved the fertility rates in jennies. The deep horn inseminations using frozen-thawed donkey semen increased the pregnancy rate in jennies, and the multiple inseminations may be an option to improve the fertility rates of donkey semen in jennies.
Keywords: Donkey jack; Equus asinus; Insemination dose; Jennies; Semen cryopreservation